Phylogeography of genus Tenualosa and population structure of Tenualosa toli (Valenciennes, 1847) inferred from cytochrome b mitochondrial DNA - Puvanasundram, Puvaneswari (2017)
This study was conducted to examine the systematic and evolutionary relationship among members of genus Tenualosa as well as genetic diversity of Tenualosa toli from selected populations in Sarawak using cytochrome b (cyt b), mitochondrial Deoxyribonucleic acid (mtDNA). A total of 111 T. toli, 24 T. macrura and four T. ilisha samples were obtained. All T. toli and T. macrura samples were collected from various localities in Sarawak and imported samples were collected from Satok market, Sarawak. Samples of T. toli were collected from Sebuyau (N= 25), Sadong Jaya (N=20), Satok market (N=9), Batang Lupar (N=20), Daro (N=12) and Mukah (N=25). Samples of T. macrura on the other hand, were collected from Sadong Jaya (N= 7), Kota Samarahan (N=11) and Daro (N=6). Tenualosa ilisha samples were obtained from Bangladesh. These samples in the form of muscle tissue and fin clips were stored in 95% ethanol before being stored in -20°C freezer for long term storage. Polymerase Chain Reaction (PCR) was conducted on samples using cyt b primer and products were then sent for sequencing. All the sequences obtained were first validated through Basic Local Alignment Search Tool (BLAST) analysis. Phylogenetic analysis supported the monophyletic status between the three species of shad. Pairwise genetic distance (13.9%-15.3%) between species in genus Tenualosa supports the taxonomic status of T. toli and T. macrura as distinct species. Nucleotide diversity in all populations were low (0.001) and the haplotype diversity ranged from the lowest value of 0.417 (Imported Toli shad) to the highest value of 0.656 (Sebuyau samples). Gene flow (Nm) was equal to infinite among all the populations of T. toli in Sarawak showing very high gene flow between them due to homogeneity of terubok population from different parts of Sarawak as T. toli move from different rivers for spawning. Pairwise fixation index (Fst) values for genetic differentiation among population showed significant levels of genetic differentiation in all comparisons between imported samples from India of T. toli population and samples obtained from Sarawak. However, there were no significant differences recorded in pairwise Fst values in most comparisons among populations of Toli shad collected from Sarawak. Analysis of molecular variance (AMOVA) results revealed that the majority of variance including percentage of variation was among population variance. Negative Tajima’s D value was obtained for samples collected from Sebuyau, Batang Lupar, and Daro as well as imported samples which could be due to recent bottleneck events leading to population expansion. Fu’s FS showed negative value for samples obtained from Sebuyau, Batang Lupar and imported samples where this value is expected due to recent population expansion. The utilization of mtDNA cyt b in this study has managed to provide an insight on the genetic makeup of T. toli collected from five different locations in Sarawak. This study supports the high genetic differences between the imported and locally collected samples where it could mean that the imported samples belong to a different gene pool or breeding groups. This study showed that cyt b is one of the suitable genes which could be employed for the purpose of species identification, phylogeography and population structure studies.